2012
DOI: 10.1007/s12272-012-1019-5
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tissue distribution of psammaplin A, a novel anticancer agent, in mice

Abstract: This study reports the pharmacokinetics and tissue distribution of a novel histone deacetylase and DNA methyltransferase inhibitor, psammaplin A (PsA), in mice. PsA concentrations were determined by a validated LC-MS/MS assay method (LLOQ 2 ng/mL). Following intravenous injection at a dose of 10 mg/kg in mice, PsA was rapidly eliminated, with the average half-life (t(1/2, λn)) of 9.9 ± 1.4 min and the systemic clearance (CL(s)) of 925.1 ± 570.1 mL/min. The in vitro stability of PsA was determined in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…The value of V d /F for W-1 was much greater than the total body water of rats (668 mL/kg) (Davies and Morris 1993;Minematsu et al 2012), implying that drug concentration in tissues was higher than plasma. The value of CL/F was 46.56 ± 7.45, 42.55 ± 7.78 and 38.66 ± 4.57 L h -1 kg -1 for 50, 100 and 200 mg/kg, respectively, which suggested that W-1 had a rapid clearance in rats (Kim et al 2012;Chen et al 2015).…”
Section: Discussionmentioning
confidence: 90%
“…The value of V d /F for W-1 was much greater than the total body water of rats (668 mL/kg) (Davies and Morris 1993;Minematsu et al 2012), implying that drug concentration in tissues was higher than plasma. The value of CL/F was 46.56 ± 7.45, 42.55 ± 7.78 and 38.66 ± 4.57 L h -1 kg -1 for 50, 100 and 200 mg/kg, respectively, which suggested that W-1 had a rapid clearance in rats (Kim et al 2012;Chen et al 2015).…”
Section: Discussionmentioning
confidence: 90%
“…To achieve optimized LC condition, several kinds of columns were tested in our preliminary study (data not shown) based on studies by Kim et al [30]. Among them, Synergi TM 4 Hydro-RP 80 Å column (75 × 2.0 mm; Phenomenex, CA, USA) provided best peak symmetry, short run time, and decent signal response, thus it was selected in this investigation.…”
Section: Lc-ms/ms Optimizationmentioning
confidence: 99%
“…The best peak shape and shortest retention time of analytes were observed at 0.4 mL/min flow rate. Therefore, compared to the method by Kim et al [30], simultaneous analyses of the three PsA derivatives with improved mobile phase conditions and run time has been achieved. Moreover, in the preliminary study, acetonitrile was used for the precipitation of plasma proteins and this sample pretreatment method provided Table 1 Within-and between-run precision and accuracy for PsA and its derivatives in rat plasma.…”
Section: Lc-ms/ms Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their multi(epi)target features and their action in ex vivo samples, psammaplin A and its derivatives are attractive molecules for the modulation of epigenetic disorders [119,120]. Recent pharmacokinetics and tissue distribution studies indicate a preferential distribution of psammaplin A to lung, suggesting the potential of this compound as a lung cancer treatment agent [121].…”
Section: Compounds That Inhibit the Extracellular Matrix Remodellingmentioning
confidence: 99%